The New Testament documents are they reliable? - Bruce, Frederick Fyvie, 1910-90 (Leicester, UK IVP, 1981)
Includes bibliographical references and indexes.
First published with title "Are the New Testament documents reliable?", in 1943.
Keywords: Bible. N.T. -- criticism, interpretation, etc